2021
DOI: 10.1002/ptr.7264
|View full text |Cite
|
Sign up to set email alerts
|

Current clinical developments in curcumin‐based therapeutics for cancer and chronic diseases

Abstract: Funding information DAICENTERThe last decade has seen an unprecedented rise in the prevalence of chronic diseases worldwide. Different mono-targeted approaches have been devised to treat these multigenic diseases, still most of them suffer from limited success due to the offtarget debilitating side effects and their inability to target multiple pathways. Hence a safe, efficacious, and multi-targeted approach is the need for the hour to circumvent these challenging chronic diseases. Curcumin, a natural compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 290 publications
(317 reference statements)
0
25
0
Order By: Relevance
“…Curcumin is a polyphenolic derivative of turmeric known to have dramatic anticancer effects on cancer cells rather than normal ones. It has been demonstrated that curcumin exerts its toxic effects through modulation of the function of multiple genes including apoptotic, metastatic, cell proliferation and transcription factors [ 10 ]. Studies reported that curcumin modulates cellular pathways involved in cancer pathogenesis including NF-kB, MAPK, PTEN, P53 and wnt [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a polyphenolic derivative of turmeric known to have dramatic anticancer effects on cancer cells rather than normal ones. It has been demonstrated that curcumin exerts its toxic effects through modulation of the function of multiple genes including apoptotic, metastatic, cell proliferation and transcription factors [ 10 ]. Studies reported that curcumin modulates cellular pathways involved in cancer pathogenesis including NF-kB, MAPK, PTEN, P53 and wnt [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin can positively affect different risk factors for CVDs and the outcome in the diseases themselves which has been shown in a number of animal models. More importantly, it is effective against cardiovascular diseases and has shown a promising impact on cardiovascular diseases in clinical studies [187]. Unfortunately, the low aqueous solubility and absorption in the gastrointestinal tract of free curcumin result in a poor pharmacokinetic profile and bioavailability.…”
Section: Future Directionsmentioning
confidence: 99%
“…Chronic disease or non-communicable disease is an umbrella term that is used to define a large number of ailments, including cancer, cardiovascular diseases (CVDs), chronic respiratory diseases, and diabetes [ 1 , 2 ]. Despite remarkable improvements in the prevention and therapy of multigenic chronic diseases, their prevalence among patients has not reduced [ 1 ].…”
Section: Introductionmentioning
confidence: 99%